Occupational anaphylaxis – an EAACI task force consensus statement. Issue 2 (February 2015) - Siracusa, A.; Folletti, I.; Gerth van Wijk, R.; Jeebhay, M. F.; Moscato, G.; Quirce, S.; Raulf, M.; Ruëff, F.; Walusiak‐Skorupa, J.; Whitaker, P.; Tarlo, S. M.
Abstract Anaphylaxis is a systemic allergic reaction, potentially life‐threatening that can be due to nonoccupational or, less commonly, to occupational triggers. Occupational anaphylaxis (OcAn) could be defined as anaphylaxis arising out of triggers and conditions attributable to a particular work environment. Hymenoptera stings and natural rubber latex are the commonest triggers of OcAn. Other triggers include food, medications, insect/mammal/snake bites, and chemicals. The underlying mechanisms of anaphylactic reactions due to occupational exposure are usually IgE‐mediated and less frequently non‐IgE‐mediated allergy or nonallergic. Some aspects of work‐related allergen exposure, such as route and frequency of exposure, type of allergens, and cofactors may explain the variability of symptoms in contrast to the nonoccupational setting. When assessing OcAn, both confirmation of the diagnosis of anaphylactic reaction and identification of the trigger are required. Prevention of further episodes is important and is based on removal from further exposure. Workers with a history of OcAn should immediately be provided with a written emergency management plan and an adrenaline auto‐injector and educated to its use. Immunotherapy is recommended only for OcAn due to Hymenoptera stings.